Best before : videogames, supersession and obsolescence - Newman, James (Routledge, 2012)
Despite record sales and an ever-growing global industry, the simple fact is that videogames are disappearing. Most obviously, the physical deterioration of discs, cartridges, consoles and controllers means that the data and devices will crumble to dust and eventually will be lost forever. However, there is more to the disappearance of videogames than plastic corrosion and bit rot. Best Before examines how the videogames industry's retail, publishing, technology design, advertising and marketing practices actively produce obsolescence, wearing out and retiring old games to make way for the always new, just out of reach, 'coming soon' title and 'next generation' platform. Set against the context of material deterioration and the discursive production of obsolescence, Best Before examines the conceptual and practical challenges faced within the nascent field of game preservation. Understanding videogames as rich, complex and mutable texts and experiences that are supported and sustained by cultures of gameplay and fandom, Best Before considers how - and even whether - we might preserve and present games for future generations.
Keywords: Video games : Marketing; Video games : Social aspects; Video games; Video games industry; markkinointi; digitaaliset pelit; tietokonepelit; videopelit; peliteollisuus